Empowering rural service providers to improve nutrition in mountain regions - Sabir, Ghezal; Bernet, Thomas; Riar, Amritbir (Frontiers in Sustainable Food Systems, 2023)
Improved agroecological practices tend to lead to production diversity but often need to be more sufficient in achieving optimal dietary diversity in rural contexts. Thus, multi-prong interventions involving consumption, knowledge and skill development for production and consumption are needed. This study assesses nutrition and production-related interventions implemented in the East African Highlands, Pamir-Tian Shan, Hindukush and the Andes. Overall, 601 rural service providers were trained and supported to implement various nutrition-sensitive agroecological interventions. Study results show that these interventions have significantly increased the intake of flesh food, eggs, vitamin A-rich leafy greens, and vitamin-A-rich vegetables and fruits. Thus this study highlights the crucial role of rural service providers in catalyzing nutrition-related change in mountain contexts.